Effects of the administration of epidermal growth factor receptor specific inhibitor cetuximab, alone and in combination with cisplatin, on proliferation and apoptosis of Hep-2 laryngeal cancer cells. Issue 10 (October 2014) - Bussu, F; Pozzoli, G; Giglia, V; Rizzo, D; Limongelli, A; De Corso, E; Graziani, C; Paludetti, G; Navarra, P; Almadori, G
Abstract Background: Epidermal growth factor receptor (EGFR) overexpression and prognostic value in head and neck squamous cell cancer is the basis for targeting by anti-EGFR antibodies, which increase the efficacy of radiotherapy. In order to evaluate the best therapeutic schedule, the effects of cetuximab (C225) on Hep-2 cell proliferation, alone and in combination with cisplatin, were studied. Methods: Hep-2 cells were treated with cetuximab alone or in combination with cisplatin. After determining cell viability with trypan blue, morphological features of apoptotic degeneration were analysed by fluorescence microscopy with Hoechst 33258 stain. Results: Cetuximab alone mildly inhibited Hep-2 proliferation and showed no pro-apoptotic effects. When administered concomitantly with cisplatin, cetuximab synergistically increased inhibition of proliferation and apoptosis. Conclusion: The antiproliferative activity of cetuximab is consistent with its hypothesised role in inhibiting repopulation. However, the increase in the effects of pro-apoptotic agents induced by cetuximab may be even more relevant to its clinical effectiveness than the inhibition of repopulation.